PENGAWASAN TENAGA KERJA ASING (TKA) OLEH PEMERINTAH PUSAT DAN DAERAH DI KABUPATEN SOLOK SELATAN - Deswinda Eka Putri; Nora Eka Putri (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aims to examine the supervision of Foreign Workers (TKA) by the Central and Regional Governments in South Solok Regency. This research was conducted at the Department of Manpower and Transmigration, West Sumatra Province, UPTD Labor Inspection Region III West Sumatra Province and the Immigration Office Class I TPI Padang. The method used in this research is to use a qualitative method with a descriptive approach through interview techniques and documentation in data collection. The results showed that the supervision of Foreign Workers (TKA) by the central and regional governments in South Solok Regency had not been running optimally because there were many obstacles that had to be faced by relevant institutions and agencies tasked with overseeing this TKA. Human resources are still lacking, the limited budget provided for supervision activities as well as the lack of facilities and infrastructure needed, especially operational vehicles. This needs to get the attention of the central government so that this monitoring activity can run more optimally.